2021
DOI: 10.9734/ajess/2021/v16i130391
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Personnel in Accreditations in Higher Educational Institution: Concerns and Actions

Abstract: Aims: To determine the experiences of the participants who were involved in the accreditation process Study Design:  Qualitative-phenomenology Place and Duration of Study: Southern Philippines Agribusiness and Marine and Aquatic School of Technology for five months. Methodology: The participants were 12 program area leaders, and Internal Assessment Board in-charge. They were grouped into four and interviewed using the validated interview guide questionnaire. Results: Themes which concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Galvez and Fuentes [19] carried out an empirical study in an education institution in the Philippines and concluded that accreditation preparations should not be initiated shortly before the expected accreditation visit; rather, preparations should start right after the previous visits so that quality activities can be carried out in true spirit. Bigdeli et al [20] investigated the accreditation experiences of top managers at the Iran University of Medical Sciences and found that experiential assistance is essential for management and academic members to face accreditation issues.…”
Section: Related Workmentioning
confidence: 99%
“…Galvez and Fuentes [19] carried out an empirical study in an education institution in the Philippines and concluded that accreditation preparations should not be initiated shortly before the expected accreditation visit; rather, preparations should start right after the previous visits so that quality activities can be carried out in true spirit. Bigdeli et al [20] investigated the accreditation experiences of top managers at the Iran University of Medical Sciences and found that experiential assistance is essential for management and academic members to face accreditation issues.…”
Section: Related Workmentioning
confidence: 99%
“…Accordingly, the nursing documentation framework needs to be standardized, reasonably organized, and structured to mirror the phases of the nursing process, i.e., the assessment, diagnosis, planning, implementation, and evaluation of patient conditions [5]. Despite the importance of clinical documentation, currently, there are undesirable situations of care recordings and a lack of an appropriate framework for documenting nursing care [6]. Studies in Iran have revealed that the nursing documentation is not compliant with the standards.…”
Section: Introductionmentioning
confidence: 99%